Sinister Tuberculous Broncho-Pleural Cutaneous Fistula: Simple Technique for A Complex Phenomenon - Yusoff M.F.M.; Haron H.; Daud W.O.W.; Aragena D.; Ismail M.I.; Md Ali N.A.; Rahman M.R.A. (Surgical Society of Northern Greece, 2024)
Indexed by Scopus